Mutanlallemand (mtl) and Belly Spot and Deafness (bsd) are two new mutations of Lmx1a causing severe cochlear and vestibular defects. - Georg Steffes; Beatriz Lorente-Cánovas; Selina Pearson; Rachael H Brooker; Sarah Spiden; Amy E Kiernan; Jean-Louis Guénet; Karen P Steel (PLoS ONE)
Mutanlallemand (mtl) and Belly Spot and Deafness (bsd) are two new spontaneous alleles of the Lmx1a gene in mice. Homozygous mutants show head tossing and circling behaviour, indicative of vestibular defects, and they have short tails and white belly patches of variable size. The analysis of auditory brainstem responses (ABR) showed that mtl and bsd homozygotes are deaf, whereas heterozygous and wildtype littermates have normal hearing. Paint-filled inner ears at E16.5 revealed that mtl and bsd homozygotes lack endolymphatic ducts and semicircular canals and have short cochlear ducts. These new alleles show similarities with dreher (Lmx1a) mutants. Complementation tests between mtl and dreher and between mtl and bsd suggest that mtl and bsd are new mutant alleles of the Lmx1a gene. To determine the Lmx1a mutation in mtl and bsd mutant mice we performed PCR followed by sequencing of genomic DNA and cDNA. The mtl mutation is a single point mutation in the 3' splice site of exon 4 leading to an exon extension and the activation of a cryptic splice site 44 base pairs downstream, whereas the bsd mutation is a genomic deletion that includes exon 3. Both mutations lead to a truncated LMX1A protein affecting the homeodomain (mtl) or LIM2-domain (bsd), which is critical for LMX1A protein function. Moreover, the levels of Lmx1a transcript in mtl and bsd mutants are significantly down-regulated. Hmx2/3 and Pax2 expression are also down-regulated in mtl and bsd mutants, suggesting a role of Lmx1a upstream of these transcription factors in early inner ear morphogenesis. We have found that these mutants develop sensory patches although they are misshapen. The characterization of these two new Lmx1a alleles highlights the critical role of this gene in the development of the cochlea and vestibular system.